nﬂuence of bischoﬁte solution on the reproductive sphere of Ambrosia artemisiifolia within the limits of industrial ground of Private joint stock company “Inguletsky Ore mining and processing plant” (Ecological Bulletin of Kryvyi Rih District, 2019)
Repressing and eliminate inﬂuence of 35% bischoﬁte solutionis revealed on the reproductive sphere of Аmbrosia artemisiifolia. Abnormal and sterile antheriferous grains increased because of Аmbrosia artemisiifolia’s sprinkling with bischoﬁte solution
Keywords: Аmbrosia artemisiifolia; pollen; bischoﬁt; industrial ground